2010
DOI: 10.1016/j.gca.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Methyl mercury distributions in relation to the presence of nano- and picophytoplankton in an oceanic water column (Ligurian Sea, North-western Mediterranean)

Abstract: Recent findings on the distribution of methylated mercury (MeHg T ) in waters have highlighted the importance of organic carbon remineralization on the production of these compounds in the open ocean. Here, we present the first time-series (20 monthly samplings between July 2007 and May 2009) of high-resolution vertical profiles (10-12 depths in a 2350 m water column) of MeHg T distributions in an open ocean environment, the Ligurian Sea (North-western Mediterranean Sea). Concentrations varied within the sub-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
164
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 61 publications
(83 reference statements)
13
164
0
Order By: Relevance
“…Stepwise regression analysis on a suite of parameters shows that nitrate alone explains 90% of the variability in measured methylation rates (P < 0.01). We postulate that this finding reflects the association between the degradation of organic matter in surface waters and MeHg production proposed by others (7)(8)(9)(10).…”
Section: Mehg Production In Estuarine Seawatersupporting
confidence: 85%
See 2 more Smart Citations
“…Stepwise regression analysis on a suite of parameters shows that nitrate alone explains 90% of the variability in measured methylation rates (P < 0.01). We postulate that this finding reflects the association between the degradation of organic matter in surface waters and MeHg production proposed by others (7)(8)(9)(10).…”
Section: Mehg Production In Estuarine Seawatersupporting
confidence: 85%
“…Prior work in the upper ocean suggests that production of methylated Hg species is linked to heterotrophic bacterial activity responsible for the turnover of organic carbon in the marine water column, as reflected by changes in nitrate, phosphate, AOU, and OCRR (7)(8)(9)(10)(11). Lake Melville is oligotrophic, and nitrate concentrations in inflowing tributaries are low (<3 μM).…”
Section: Mehg Production In Estuarine Seawatermentioning
confidence: 99%
See 1 more Smart Citation
“…[15] In other oceans, it has recently been demonstrated that MeHg can be produced during the remineralisation of algal detritus in the water column. [44,86,98,99] The vertical transport of MeHg associated with particulate flux from surface waters was found to be relatively unimportant compared with the in situ production of MeHg that occurred in association with nutrient maxima at subsurface water depths. [86] Little is known about this process in the Arctic; however, the Arctic Ocean does possess pervasive strong nutrient maxima below the polar mixed layer.…”
Section: Microbial Carbon Processing and Mercury In The Arcticmentioning
confidence: 95%
“…As DMHg is not bioaccumulated and because its Hg isotopic composition has not been measured, it is not treated in detail here. MMHg production in the oxygen minimum zone (OMZ) of the oceanic water column has been hypothesized 7,13 and recent field studies have offered new evidence supporting in situ methylation not only in OMZs (refs 3,6) but also in oxic surface waters 4,5,[15][16][17] . Vertical differences in ocean biogeochemistry and the relative contributions of different Hg sources to the overall MMHg burdens in fish have wide-ranging implications for understanding how MMHg levels in marine biota will respond to future changes in anthropogenic Hg emissions 3,18 .…”
mentioning
confidence: 99%